Mood and physical activity are associated with appetite in hospitalised older men and women. (29th December 2022) - Cox, Natalie J; Howson, Fiona; Ibrahim, Kinda; Morrison, Leanne; Sayer, Avan A; Roberts, Helen C; Robinson, Sian M
Abstract: Background: The anorexia of ageing is important in the development of malnutrition, frailty and sarcopenia amongst the older population and is a particular problem for hospital inpatients. This study assessed appetite-related factors in a group of hospitalised older adults, to identify potential preventive strategies. Design: Cross sectional observational study. Setting: Eleven wards in one large hospital in England. Subjects: Older inpatients aged ≥70 years, admitted non-electively. Methods: Appetite was assessed using the four-item Simplified Nutritional Appetite Questionnaire (SNAQ). Associations between SNAQ score and appetite-related factors present in the dataset were assessed in continuous analyses, including habitual physical activity, mood, medication, cognition and living circumstances. Results: 200 participants, mean age of 80.7 years (SD 6.9); 40% were women. Prevalence of poor appetite was 43%. In univariate analyses, lower medication count, higher habitual physical activity and better mood were associated with higher SNAQ scores during admission. In a multivariate analysis, independent associations of higher habitual physical activity and better mood with higher SNAQ scores during hospital admission remained. Conclusion: In this group of older adults, better mood and higher habitual physical activity were independently associated with better appetite during hospital admission. These are potentially modifiable factors and could be targets for future research into interventions for the anorexia of ageing in the hospitalised older population.